SUCCESS RATE OF MEDCEM PORTLAND CEMENT AS A PULP CAPPING AGENT IN PULPOTOMIES OF PRIMARY TEETH - Veronika Marie Vilimek (Journal of IMAB, 2018)
Aim: To evaluate the clinical and radiographic outcomes of Portland cement (PC) as a pulp capping agent in primary teeth pulpotomies. Material and methods: The study included 71 primary teeth (9 incisors and 62 molars), from 20 children aged 3-8 years, of both genders. The teeth had deep carious lesions and symptoms of inflammation of the coronal pulp. Treatment was performed under general anaesthesia, and with the technique of vital amputation. MedCem Portland cement was used as pulp capping agent. GIC was placed over the PC. Incisors were finally restored with composite and molars with preformed stainless steel crowns. Clinical and radiographic success and failure were recorded at 6, 12, 18 and 24-month follow-ups. The treatment success was measured using predetermined criteria and the results were statistically evaluated. Result: After 12 months 69 teeth (97.18%) were assessed as successfully treated. After 24 months, the treatment of 66 teeth (92.96%) were defined as successful. The results showed a satisfactory success rate of pulpotomies using MedCem PC as a pulp agent in the primary dentition during the observation period. Conclusions: Portland cement may serve as an effective and inexpensive material in primary teeth pulpotomies. Further studies and longer follow-up assessments are needed.